An analytical framework to examine power in sustainable energy decision-making in cities - Basu, Sumedha (Frontiers in Sustainable Energy Policy, 2024)
Urban areas are emerging as “strategic sites” in the ongoing sustainable energy (SE) transitions. This has rekindled the importance of urban governments in initiating this transition urgently, a departure from the actors managing more mainstream centralized energy governance. However, while there is a growing international and academic interest in urban energy transitions, the political presence of cities in the global clean energy landscape remains largely underwhelming. Scholars studying urban energy transitions or governance have often pointed toward the lack of material and knowledge capacities of the urban governments as the key barrier for their muted actions. I argue that decision-making by urban governments with respect to clean energy adoption needs deeper inspection wherein aspects such as capacity, or the lack of it, are symptoms of underlying power contestations and conflicts that are negotiated in multi-level governance systems. The scholarship of power captures the ideas of contestation, control, and acquiescence, going beyond the ideas of cooperation prevalent in multilevel governance. In this article, I juxtapose these with concepts from multi-level governance and socio-technical studies to offer an analytical framework for understanding energy decision-making by city governments. The framework presented in this article attempts to capture both direct and indirect forms of power, their operationalization, and manifestation in constituting identities, actual decisions (and indecisions) as well as the conditions of decision-making. I also use the framework to understand the role of power in sustainable energy decision-making in three cities in India as an illustration of possible application of the framework.